Pengaruh Persepsi Harga dan Kualitas Pelayanan terhadap Loyalitas Pelanggan Dimediasi Kepuasan Konsumen Pada RM. Wongsolo Malang - Dewi, Mariana Puspa (Fakultas Ekonomi, UIN Maliki Malang, 2020)
The objective of this research is to: (1) Review and analyze the effect of price perception based on customer loyalty of RM. Wong Solo Malang, (2) Review and analyze the effect of service quality to customer loyalty, (3) Review and analyze the effect of price perception through consumer satisfaction, (4) Review and analyze the effect of service quality through consumer satisfaction to customer loyalty, (5) Review and analyze the effect of consumer satisfaction to customer loyalty. This research type is a quantitative study in the form of a causal relationship. The population in this research was 100 consumers in RM. Wong Solo Malang. The technique used in this research is an accidental sampling. The analysis used is path analysis. The results of this research show that : (1) Price perception has a positive and significant effect on customer loyalty of RM. Wong Solo Malang, 2) Service quality has a positive and significant effect on customer loyalty, 3) Price perception has a significant effect on customer loyalty based on consumer satisfaction, 4) Service quality has a significant effect on customer loyalty based on consumer satisfaction, 5) Consumer satisfaction has a significant effect on price perception and quality service to customer satisfaction.